Colorectal Cancer Patients Have Four Specific Bacterial Species in Oral and Gut Microbiota in Common—A Metagenomic Comparison with Healthy Subjects - Uchino, Yoshinori; Goto, Yuichi; Konishi, Yusuke; Tanabe, Kan; Toda, Hiroko; Wada, Masumi; Kita, Yoshiaki; Beppu, Mahiro; Mori, Shinichiro; Hijioka, Hiroshi; Otsuka, Takao; Natsugoe, Shoji; et al. (Cancers, 2021)
Oral microbiota is reportedly associated with gut microbiota and influences colorectal cancer (CRC) progression; however, the details remain unclear. This study aimed to evaluate the role of oral microbiota in CRC progression. Fifty-two patients with CRC and 51 healthy controls were included. Saliva and stool samples were collected, and microbiota were evaluated using 16S rRNA analysis and next-generation sequencing. Comparative analysis was performed on both groups. Linear discriminant analysis effect size (LEfSe) revealed the presence of indigenous oral bacteria, such as Peptostreptococcus, Streptococcus, and Solobacterium spp., at a significantly higher relative abundance in saliva and stool samples of CRC patients compared with controls. Next, CRC patients were divided into early stage (Stage I, II; n = 26; 50%) and advanced stage (Stage III, IV; n = 26; 50%) disease. LEfSe revealed that S. moorei was present at a significantly higher relative abundance in the advanced-stage group compared with the early-stage group, again consistent for both saliva and stool samples. Among bacterial species with significantly higher relative abundance in CRC patients, P. stomatis, S. anginosus, S. koreensis, and S. moorei originated from the oral cavity, suggesting indigenous oral bacteria may have promoted initiation of CRC carcinogenesis. Furthermore, S. moorei may influence CRC progression.